Importance of studies on aging processes of animals in the search for means to prolog human life (II. Physiological, Metabolic and Biochemical Changes, Gerontological Tissue Cultures and DNA Injury and Repair) - ΧΑΤΖΗΟΛΟΣ Β. Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Among the organs which undergo serious changes is the skeletal muscle, which, with the heart and brain, is made up of irreplaceable postmitotic cells. The physiological disturbances of this tissue are manifested by an increasing reduction of its function, similar to that observed in older flying insects, whose muscular structure resembles that of vertebrates, including man. A similar reduction has also been observed in the energy-producing enzymes of the myocardium of aging white rats. The metabolic disturbances during aging discussed here concern: (a) proteins which show increased excretion of Ν in the urine in cases of injury, (b) carbohydrates and lipids associated with diabetes and arteriosclerosis, which may constitute the final phase of the effects of obesity by creating first, a compensatory hyperinsulinism and second, following a hyperinsulinemia due to faulty regulation of the insulin receptors, a reactive insulin deficiency caused by-cell exhaustion, and (c) connective tissue, particularly the collagene with their metabolic steps, i.e., the effects of peptidyl hydroxilation, the role of hydroxyproline and hydroxylysine, the agedependent control of prolyl hydroxylation in the culture of WI-38 fibroblasts, and finally, the changes in cell-surface associated proteins, Including an increase in the production of fibronectin with age, and its repercussions on the physiology of certain epi-endothelial cells. Also reviewed are some of the latest findings in gerontological research on: cells in culture including the WI-38 fibroblasts, the relationship among aging cells in vivo, the loss of mitotic activity and the possibility of cell differentiation of the idle skin cells, the aging process as observed in the cell culture system, the behavior of normal cells, the cellular aspects of senescence and the acquisition of sensitivity of the normal cells to one another, the incompatibility of cell growth and division, and the inverse relationship between the life span of cells in culture to the age of the donor, among others. Reference is also made to the role of histories and the possibility of an active gene that controls aging. Other subjects include the mechanism of synthesis and degradation of proteins, the damage and repair of DNA, the importance of in vivo examination of various types of DNA injury, the role of the RNA and that of the cell membrane In Ca transfer and contractibility of the heart muscle, the gene expression, the possible chromatin damage involved, the products of histone metabolism, the probable role of acctylation, and the manner of aging of various systems, organs, and cells.